Market for university education in Singapore - Cai, Alma Wanting (2008)
This project seeks to understand the future position of Singapore in the world market place as an education provider. Our group’s main emphasis is not on the objective part, but rather on the subjective part. We seek to find out more about what people look for in and want out of an educational system and the reasons for obtaining what they want either locally or abroad.